Association of genetic polymorphisms in XRCC4, XRCC5, XRCC6 and XRCC7 in cervical cancer susceptibility from rural population: a hospital based case-control study - Datkhile, Kailas D.; Patil, Madhavi N.; Durgawale, Pratik P.; Korbu, Kalpita S.; Joshi, Shreepad A.; Kakade, Satish V. (International Journal of Research in Medical Sciences, 2018)
Background: Cervical cancer is a major concern of health risk, moreover the leading cause of cancer causing deaths in women of rural India. This study was aimed to assess the risk of cervical cancer development in association with polymorphisms in XRCC4, XRCC5, XRCC6 and XRCC7 genes in rural population of south-western Maharashtra. Methods: This study included 350 cervical cancer proven cases and 400 age and sex matched controls. We used polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) to analyze the association XRCC4, XRCC6 and XRCC7 gene polymorphisms with cervical cancer development in women of Western Maharashtra. Results: The result from our study showed that allele frequencies of selected genes were not statistically different between the groups for XRCC4, XRCC5 and XRCC6. 6721 >T allele of XRCC7 (6721G>T) (OR= 2.34; 95% CI= (2.34 (1.60-3.43); p= <0.0001) significantly increased the risk of cervical cancer. Conclusions: This study indicates that XRCC7 gene polymorphisms play a role in modifying genetic susceptibility of individuals towards cervical cancer among women from rural Maharashtra. This case-control study also revealed negative association of XRCC6 gene in cervical carcinogenesis in the rural Indian population.